The conundrum of predicting neurological outcomes in non-traumatic coma patients: True prediction or "Flipping a Coin" - Mpouzika, Meropi; Karanikola, Maria; Blot, Stijn I. (My University, 2024)
Coma, as a transitory state of eyes-closed deep unresponsiveness, is characterized by unconsciousness and entails a severe disturbance of arousal and alerting functions, inappropriate response to stimuli, and alteration of awareness and the content of consciousness ( Huff and Tadi, 2023 ). Common causes of non-traumatic coma (NTC) include stroke, post-anoxic coma post-cardiac arrest, poisoning, metabolic disorders, and infections
Keywords: Coma; Humans; Predictive Value of Tests; Prognosis; Pathophysiology